Studies on Schismatoglottideae (Araceae) of Borneo LVII: Bucephalandra filiformis – a new species from Maligan, Sarawak, Malaysian Borneo - Wong, Sin Yeng; Boyce, P.C (International Aroid Society, Inc., 2016)
Bucephalandra filiformis is described as a new species with uniquely stiff linear leaf blades, illustrated from living plants from the Maligan Range (Sarawak & Sabah, Malaysian Borneo), and inserted into the most recent identification key to Bucephalandra species.